Juridical review of pastoral mediation in divorce cases of catholic married couples - Dian Ety Mayasari,; L. Budi Kagramanto,; Endang Prasetyawati,; Yovita Arie Mangesti, (Technium Social Sciences Journal, 2023)
The provision in Article 2 of Marriage Law involves the religious values of marriage sacredness to legalize marriage. However, no explicit involvement of religious law was found in the divorce settlement as has been regulated in Article 39 paragraph 1 of Marriage Law stating that divorce can only be granted in front of a court session after the court has tried and failed to reconcile the two parties. Mediation process requires a mediator other than the judge, as regulated in Article 19, paragraph (1) of Supreme Court Regulation No. 1 of 2016 on Mediation in Court Procedure. This paper focuses on Catholic married couple who filed a divorce application at District Court and involved pastor as the mediator for both parties. Pastors can be involved in divorce mediation of a Catholic married couple as regulated in Article 26 paragraph (1) of Supreme Court Regulation No 1 of 2016 concerning in-court Mediation Procedure that allow religious leader to serve as the mediator to reconcile a married couple who apply for a divorce. Therefore, the judge who presided over the divorce case can reject the divorce application filed by a Catholic married couple without pastoral consultation or mediation.